Magical Habits - Huerta, Monica, 1981- (Book collections on Project MUSE., 2021)
"Monica Huerta draws on her experiences growing up in her family's Mexican restaurants and her life as an academic to sketch out habits of living that allow us to consider what it means to live with history as we are caught up in it and how those histories bear on our capacities to make sense of our lives."--